Resisting Elitist Branding: Counter-Narratives and Symbolic Resistance of Local Tourism Actors in Labuan Bajo, Indonesia - hudiono, Rini kartika; Lasso, Aldi Herindra; Prabawa, Titi Susilowati (Institut Pariwisata dan Bisnis Internasional, 2025)
Much of the destination branding literature continues to frame branding as a largely technical marketing exercise, paying limited attention to how branding operates as a contested social process shaped by unequal power relations. This study intervenes in that debate by exploring how local tourism actors in Labuan Bajo, Indonesia—officially designated as a “super-priority destination” since 2019—respond to the state-led Enchanting Labuan Bajo branding through everyday counter-branding practices. Based on nine months of critical ethnographic fieldwork, the study draws on in-depth interviews with local accommodation owners, local boat owners, and local tour guides, complemented by focus group discussions with the Wae Kelambu Women’s Community and sustained participant observation. Analytical engagement with moral economy, epistemic justice, and Scott’s concept of hidden transcripts reveals that destination branding is experienced locally not merely as promotion, but as a form of symbolic imposition that marginalizes local identities and constrains meaningful participation. Importantly, local responses were far from homogeneous. Tour guides articulated epistemic resistance by asserting their authority as cultural knowledge holders; boat owners enacted material–ecological resistance to defend long-standing access to the sea; while accommodation providers, particularly women-led guesthouses, mobilized moral–symbolic resistance through care-based hospitality practices. The article’s main theoretical contribution lies in reframing counter-branding not as evidence of branding failure, but as an alternative mode of participation that emerges when formal participatory mechanisms are inaccessible or ineffective. From this perspective, counter-branding signals deeper participatory deficits rather than marketing shortcomings, pointing to the need for destination governance approaches that prioritize inclusive and dialogical engagement over compliance-driven branding implementation.